2020
DOI: 10.1093/alcalc/agaa021
|View full text |Cite
|
Sign up to set email alerts
|

Factor, Concurrent and Predictive Validity of the Readiness to Change Questionnaire [Treatment Version] Among Non-Treatment-Seeking Individuals

Abstract: Aims This study assessed the factor, concurrent and predictive validity of the revised Readiness to Change Questionnaire [Treatment Version] (RCQ[TV]) among non-treatment-seeking individuals. Methods Non-treatment-seeking patients (Mage = 34.8, SD = 12.4) who screened positive for alcohol misuse were recruited from three urban Level I Trauma Centers and completed the RCQ[TV] (Heather et al. [(1999) Development of a treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(17 citation statements)
references
References 37 publications
2
15
0
Order By: Relevance
“…That is, those higher in contemplation at the 3‐month follow‐up are more likely to engage in at‐risk drinking, drink more, and experience alcohol problems up to 1 year later. These findings are consistent with a previous analysis of these data which found that higher contemplation scores predicted more alcohol use at 3‐month follow‐up (Richards et al, 2020). Further, these findings suggest that additional intervention may be required for those who remain ambivalent about making changes in their drinking at 3 months.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…That is, those higher in contemplation at the 3‐month follow‐up are more likely to engage in at‐risk drinking, drink more, and experience alcohol problems up to 1 year later. These findings are consistent with a previous analysis of these data which found that higher contemplation scores predicted more alcohol use at 3‐month follow‐up (Richards et al, 2020). Further, these findings suggest that additional intervention may be required for those who remain ambivalent about making changes in their drinking at 3 months.…”
Section: Discussionsupporting
confidence: 93%
“…That is, motivation to change may mediate the effects of the brief interventions compared to BA. Consistent with expectations, our research has shown that those with more severe alcohol problems are more motivated to change their drinking at baseline (Richards et al, 2020). Given the observed moderating effect of severity of alcohol use on drinking outcomes observed in the parent study, motivation may mediate the effects of brief intervention for those with less severe alcohol problems but not those with more severe alcohol problems.…”
Section: Stages Of Change As a Mechanism Of Changesupporting
confidence: 88%
See 1 more Smart Citation
“…Further psychometric analyses revealed that eliminating the poorest performing item from each subscale (i.e., 12 items in total) resulted in improved psychometric properties and this 12-item measure was found to be both reliable and valid (Heather & Hönekopp, 2008). It stands to reason that the treatment version of the RCQ may be just as applicable, or even more so, to nontreatment-seeking populations as the original version given that the only major change was that the treatment version broadens the referenced goals to both abstinence and reductions as opposed to just reductions (Richards et al, 2020).…”
mentioning
confidence: 99%
“…Richards et al (2020) conducted the first psychometric evaluation of the 12-item treatment version of the RCQ among a nontreatment-seeking sample, specifically using data from a multisite randomized controlled trial of brief intervention for alcohol use in the trauma care setting (Field et al, 2014). Support for the three-factor structure of the RCQ at baseline was found over alternative models, specifically a single common factor model representing overall readiness (e.g., Budd & Rollnick, 1996) and a two-factor model where precontemplation (reverse scored) and contemplation items loaded onto a common factor given a high interfactor correlation.…”
mentioning
confidence: 99%